Identifying Children with Constitutional Mismatch Repair Deficiency (CMMR-D) Syndrome in the Expanding Lynch Syndrome population in Cape Town - Tu, Sindy Jen-Yi (Division of Anatomical Pathology, 2022)
INTRODUCTION: Constitutional Mismatch Repair Deficiency (CMMR-D) syndrome is a rare tumour predisposition and polyposis syndrome that presents in childhood. It is caused by mutations in mismatch repair (MMR) genes that result in a tumour spectrum including colorectal cancers, high-grade gliomas, non-Hodgkin T-cell lymphomas and leukaemias. It is characterized by biallelic germline mutation of one of four possible MMR genes resulting in loss of protein expression that can be identified by applying immunohistochemistry to formalin fixed paraffin embedded tissue sections. Use of MMR immunohistochemistry is established in the setting of Lynch syndrome (LS); however, the pattern of loss of staining in the background, non-tumour tissue is unique to CMMR-D syndrome. CMMR-D syndrome is seen in LS families and occurs as a result of consanguinity or founder effect. The South African population has LS families concentrated in the Western Cape and Northern Cape Provinces and the mixed ancestry population shows a unique MLH1 c1528C>T mutation which may have implications on the incidence, penetrance and severity of CMMR-D syndrome seen in our population. The diagnosis of CMMR-D syndrome includes clinical findings outlined in the European Consortium's Care of CMMRD document and confirmation of the biallelic mutation in one of the MMR genes. MMR immunohistochemistry can be used in the diagnosis of CMMR-D syndrome by identifying cases for targeted molecular genetic tests. However, MMR immunohistochemical staining patterns are not usually described in detail, particularly the loss of staining of the affected gene in the background, non-tumour tissue, the key feature of CMMR-D syndrome. METHODS: We performed a retrospective analysis of archival formalin fixed paraffin embedded tissue of children attending Red Cross Children's Hospital with tumours that form part of the CMMR-D spectrum, outlined by the Care for CMMRD criteria. We used the criteria of high-grade gliomas (WHO Grade III or IV) occurring before 25 years of age, cutaneous lesions suggestive of CMMR-D syndrome and patients with a first or second degree relative diagnosed with LS. MMR immunohistochemistry was applied, and the staining pattern was documented in terms of proportion of tumour staining and intensity of staining using a modified Allred Scoring system. Specific attention was given to the characterization of the staining pattern of the background normal tissue. RESULTS: 21 samples taken from 18 patients were evaluated. 16 samples represented brain tumours, predominantly high-grade gliomas. Three samples were excluded due to suboptimal staining despite positive external controls. 12 samples showed intact staining of all four MMR stains. Two samples showed staining of unknown significance. Four samples from 3 different patients showed staining patterns compatible with MMR deficiency. This included two patients, each with a biopsy showing high-grade glioma and two samples of the same patient taken at a 1-year interval of a Burkitt lymphoma. Of these four samples, three samples showed loss of staining in background non-tumour tissue with positive external control, the unique staining pattern for CMMR-D syndrome. These cases will be referred for confirmatory testing by molecular genetic techniques. CONCLUSION: MMR immunohistochemistry can be used in the evaluation of CMMR-D syndrome, but care is needed in evaluating adequacy of staining, the pattern and scoring of staining of both the tumour and the background non-tumour tissue. Endothelial cells are easy to identify and evaluate as background tissue which is useful in extra-intestinal tumours. Neurons and choroid plexus can also be evaluated as background tissue in brain tumour samples. Selection bias in this study resulted in the underrepresentation of lymphomas and colorectal carcinomas. Improved characterization and search for Non-Hodgkin T-cell lymphomas and inclusion of samples of colorectal carcinomas of adolescents and adults would be needed to include these tumours. Use of MMR immunohistochemistry in postmortem tissue samples is not recommended because of suboptimal staining, even with a short post-mortem interval of 1 day. The diagnosis of CMMR-D syndrome depends on clinical application of Care for CMMRD criteria, MMR immunohistochemistry in conjunction with molecular genetic testing. It is important to identify cases of CMMR-D syndrome and offer cancer screening to prevent development of other cancers in the index patient. It also provides an opportunity for genetic counselling and testing of the parents and at-risk siblings.